2018
DOI: 10.1186/s12936-018-2489-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal analysis of Plasmodium falciparum prevalence to understand the past and chart the future of malaria control in Kenya

Abstract: BackgroundSpatial and temporal malaria risk maps are essential tools to monitor the impact of control, evaluate priority areas to reorient intervention approaches and investments in malaria endemic countries. Here, the analysis of 36 years data on Plasmodium falciparum prevalence is used to understand the past and chart a future for malaria control in Kenya by confidently highlighting areas within important policy relevant thresholds to allow either the revision of malaria strategies to those that support pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
83
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 35 publications
7
83
1
Order By: Relevance
“…The level of multilocus non-random association in this study is lower than previously reported in areas with intense transmission, including Kenya [13,14,20,22,38]. The recent increase (2011-2014) and subsequent decline (from 2015 on) of malaria prevalence are likely to have altered the frequency of minor alleles [4,5], thus contributing to the lower LD observed here. This is demonstrated by significant multilocus LD in Asembo, western Kenya before deployment of ITNs in 1996, followed by non-significant and significant multilocus LDs in 2001 and 2007, respectively [13,14].…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The level of multilocus non-random association in this study is lower than previously reported in areas with intense transmission, including Kenya [13,14,20,22,38]. The recent increase (2011-2014) and subsequent decline (from 2015 on) of malaria prevalence are likely to have altered the frequency of minor alleles [4,5], thus contributing to the lower LD observed here. This is demonstrated by significant multilocus LD in Asembo, western Kenya before deployment of ITNs in 1996, followed by non-significant and significant multilocus LDs in 2001 and 2007, respectively [13,14].…”
Section: Discussioncontrasting
confidence: 73%
“…This was a slight reduction from the ≥ 80% prevalence reported by previous studies . Since the prevalence of polyclonal infections is proxies of malaria transmission, our findings suggest that malaria transmission intensity has decreased in line with the lower malaria prevalence in Kenya over the last three decades . However, this trend has not been observed in the genetic diversity of the Kenyan P. falciparum population as exemplified in the present and in previous studies .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Such an approach does not adjust for a) the spatial and temporal heterogeneities in the data at a more granular scale; b) the populations who would use health facilities at the borders of administrative units; or c) missingness of the reported data by health facility. Importantly, data use rarely considers uncertainty thresholds which are important metrics for decision making when choosing between malaria strategies [12,[14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This involved the introduction and scaling up of interventions such as long-lasting insecticide net (LLIN), rapid diagnostic test (RDT), and artemisinin-based combination therapy (ACT) [5,6]. The implementation of these interventions have resulted to a decline in malaria transmission in many parts of the country [7]. Nevertheless, the coastal part of the country and areas along the shores of Lake Victoria continue to face high malaria transmission [8].…”
mentioning
confidence: 99%